40 - Das reicht! - ça suffit! - [Stacheldraht vor Hügel- und Berglandschaft]
politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Friedensbewegung politischer Rahmen;politisches Leben (allgemein);politische Ideologie;Pazifismus Sicherheitspolitik;Verteidigung;Armee;Armeeabschaffung;GSoA